Determinants of E-Learning Adoption in Universities: Evidence arom A Developing Country - Ansong, E (University of Ghana, 2015)
Electronic Learning (e-learning) – the use of ICT to support learning – has become paramount in the growth of universities worldwide. Universities are now including e-learning modules in their curricula to support and in some cases replace the face-to-face educational methods. This has spurred a lot of studies into e-learning adoption in higher learning institutions. However, studies looking at e-learning adoption from a multi-stakeholder perspective are quite missing in literature, especially in developing countries. Previous studies tend to focus on one of the three major categories of e-learning stakeholders: students, instructors and administrators. Again, the studies sometimes tend to have a singular focus on e-learning adoption determinants: technological, organisational and environmental. This study, therefore, sought to explore the technological, organisational and environmental determinants of e-learning adoption in University of Ghana using a multi-stakeholder approach. Another construct (Nature of the course) was added to the traditional constructs of the Technology-Organisation-Environment (TOE) framework to underpin the study. Eight factors were identified after the review of e-learning literature: IT infrastructure, perceived ease of use, organisational compatibility, expected benefits, educational partners, competitive advantage, content of the e-learning course and e-learning curriculum. Using a quantitative survey research method, a total of 417 e-learning stakeholders in the University of Ghana responded to the questionnaire. The data was analysed by means of factor analysis, correlation and multiple regression. The findings established that IT infrastructure, organisational compatibility, expected benefits, competitive pressure, educational partners, content of the e-learning course and e-learning curriculum influence students’ adoption of e-learning. Also, perceived ease of use, educational partners and e-learning curriculum influence instructors to adopt e-learning. On the other hand, IT infrastructure, organisational compatibility and expected benefits are adoption determinant factors for the e-learning administrators. The analysis further revealed that e-learning was yet to receive a university-wide adoption and again, a more complex organisational compatibility leads to e-learning being less adopted in the institution. The findings from the study contributes to the body of knowledge by extending the Technology, Organisation and Environment framework in an e-learning study to include a fourth factor which is the Nature of the course. Again, the findings provide a multi-stakeholder perspective to the study of e-learning adoption. The originality of the study lies in the multi-stakeholder (student, instructors and e-learning Administrators) perspective with a multi-dimensional framework (Technology, Organisation, Environment and Nature of Course) approaches to the study of e-learning adoption in a developing country. The study therefore recommends that university authorities take into consideration the adoption determinant factors when introducing e-learning systems. Future studies can consider researching into mobile enabled learning (m-learning) since it is an emerging trend in the educational sector.
Thesis (MPhil) - University of Ghana, 2015